ISOLASI DAN KARAKTERISASI JAMUR SELULOLITIK DARI TANAH PERKEBUNAN TEBU DESA GUNUNG WARAS KABUPATEN WAY KANAN - Rony Setiawan; Sumardi (Cocos Bio, 2024)
Sugarcane production is increasing, but waste in sugarcane plantations is also increasing, in the form of unwanted leaves and residual sugarcane stalks, which have a high cellulose content. To handle this organic waste, biodegradation agents in the form of cellulolytic fungi can be used, so it is necessary to screen cellulolytic fungi that can thrive and adapt to the sugarcane plantation environment. Organic particles, or litter, become a place of life for microorganisms such as fungi, bacteria, and other organisms. The purpose of this study was to identify the types of cellulolytic fungi found in sugarcane plantation soil in Gunung Waras Village, Way Kanan Regency, examine the effect of temperature and pH fluctuations on these fungi, and test their pathogenicity to plants. This study produced two fungal isolates that have the ability to degrade cellulose, namely Cunninghamella sp. and Trichoderma sp., with cellulolytic indexes of 0.754 and 0.403, respectively. Both isolates were tolerant of several pH variations, and there were no significant differences at the 95% confidence interval in the mean mycelial biomass at pH 3, 5, and 7. They could grow well at 25°C but not at 45°C